Degenerate first-order inverse problems in Banach spaces - Al Horani, Mohammed; Favini, Angelo (Nonlinear analysis, 2012)
We are concerned with an inverse problem for a degenerate linear evolution equation of first-order. Both hyperbolic and parabolic cases will be considered. We indicate sufficient conditions for the existence and uniqueness of a solution. All the results can be applied to inverse problems for equations from mathematical physics. As a possible application of the abstract theorems, some examples of partial differential equations are given.